Recent Advances in Polymeric Nanomedicines for Cancer Immunotherapy. Issue 4 (22nd January 2019) - Lee, Eun Sook; Shin, Jung Min; Son, Soyoung; Ko, Hyewon; Um, Wooram; Song, Seok Ho; Lee, Jae Ah; Park, Jae Hyung
Abstract: Immunotherapy has emerged as a promising approach to treat cancer, since it facilitates eradication of cancer by enhancing innate and/or adaptive immunity without using cytotoxic drugs. Of the immunotherapeutic approaches, significant clinical potentials are shown in cancer vaccination, immune checkpoint therapy, and adoptive cell transfer. Nevertheless, conventional immunotherapies often involve immune‐related adverse effects, such as liver dysfunction, hypophysitis, type I diabetes, and neuropathy. In an attempt to address these issues, polymeric nanomedicines are extensively investigated in recent years. In this review, recent advances in polymeric nanomedicines for cancer immunotherapy are highlighted and thoroughly discussed in terms of 1) antigen presentation, 2) activation of antigen‐presenting cells and T cells, and 3) promotion of effector cells. Also, the future perspectives to develop ideal nanomedicines for cancer immunotherapy are provided. Abstract : Immunotherapy has emerged as a promising approach to treat cancer due to its significant clinical benefits. Nonetheless, conventional cancer immunotherapies often involve limitations such as immune‐related adverse effects. In an attempt to address this issue, polymeric nanomedicine has been widely investigated. In this review, the recent advances in polymeric nanomedicine for cancer immunotherapy are discussed in detail.